The effects of user generated content and firm generated content on millennials' purchase intention of shariah-compliant stocks - De Costa, Feroz; Abd Aziz, Norzalita (Penerbit Universiti Kebangsaan Malaysia, 2021)
The goal of this study is to understand how digital content marketing influences online share purchase intentions. The specific objective of this study is to determine the effect of user generated content and firm generated content on millennials’ purchase intention of online shares. The data for this study were collected using a convenience sampling approach from 308 valid online questionnaires in Malaysia and analysed using the partial least squares structural equation modelling technique (PLS-SEM). According to the findings of this study, both user-generated and firm- generated contents have a positive impact on brand attitude. The results of applying the theory of reasoned action revealed a counterintuitive result to earlier research whereby user generated content has no direct effect on the purchase intention of online stocks. Theoretical and managerial implications of financial marketing are discussed.